IMPLEMENTATION AND VALIDATION OF AN ADAPTIVE FECMECHANISM FOR VIDEO TRANSMISSION (Journal of Information and Communication Technology, 2012)
This research focuses on investigating the FEC mechanism as an error recovery over a wireless network. The existing adaptive FEC mechanism faces a major drawback, which is the reduction of recovery performance by injecting too many excessive FEC packets into the network. Thus, this paper proposes the implementation of an enhanced adaptive FEC (EnAFEC) mechanism for video transmission together with its validation process. There are two propositions in the EnAFEC enhancement, which include block length adaptation and implementation, and suitable smoothing factor value determination. The EnAFEC adjusts the FEC packets based on the wireless network condition so that excessive FEC packets can be reduced. The proposed enhancement is implemented in a simulation environment using the NS-2 network simulation. The simulation results show that EnAFEC generates less FEC packets than the other types of adaptive FEC (EAFEC and Mend FEC). In addition, a validation phase is also conducted to verify that the proposed enhancement is functioning correctly, and represents a real network situation. In the validation phase, the results obtained from the simulation are compared to the outputs of the other adaptive FEC mechanisms. The validation results show that the mechanism is successfully implemented in NS2 since the number of packet loss falls under the overlapping confidence intervals.